(untitled) (Asian Journal of Pharmaceutics (AJP), 2016)
Recent estimate revealed that in the year 2012, about 227,000 American women suffered from metastatic breast cancer (mBC). The U.S. Food and Drug Administration (FDA) have approved ado-trastuzumab emtansine (T-DM1) on 22 February 2013 for the treatment of human epidermal growth factor receptor (HER2)-positive mBC who has previously been treated with trastuzumab and a taxane. T-DM1 received the European Commission approval on November 2013 based on results from the pivotal Phase III EMILIA trial and Switzerland is the first country which has the marketing permission for T-DM1 in Europe. In September 2013, It received marketing approval in Japan based on results from a Japanese Phase II trial and the EMILIA Phase III trial and also approved by Health Canada. T-DM1 is an antibody-drug conjugate (ADC). ADC consists of monoclonal antibody trastuzumab, which covalently linked with DM1 (cytototoxin, microtubule inhibitor) by mitotic checkpoint complex (MCC) linker. The ADC delivers the toxin specifically to tumor cells. DM1 binds to tubulin, and it disrupts microtubule network in the cell. Cell cycle arrest and apoptotic cell death were occurred. In clinical trials, patients (991) were randomly assigned in a 1:1 ratio to kadcyla or lapatinib plus capecitabine. The recommended dose is 3.6 mg/kg every 3 weeks (21-day cycle).